Arterial wall inflammation is increased in rheumatoid arthritis compared with osteoarthritis, as a marker of early atherosclerosis. (14th January 2021) - Agca, Rabia; Blanken, Annelies B; van Sijl, Alper M; Smulders, Yvo M; Voskuyl, Alexandre E; van der Laken, Conny; Boellaard, Ronald; Nurmohamed, Michael T
Abstract: Objective: RA is associated with higher risk of cardiovascular (CV) disease. Ongoing systemic inflammation is presumed to accelerate atherosclerosis by increasing inflammation in the arterial wall. However, evidence supporting this hypothesis is limited. We aimed to investigate arterial wall inflammation in RA vs OA, and its association with markers of inflammation and CV risk factors. Methods: 18-fluorodeoxyglucose PET combined with CT ( 18 F-FDG-PET/CT) was performed in RA ( n = 61) and OA ( n = 28) to investigate inflammatory activity in the wall of large arteries. Secondary analyses were performed in patients with early untreated RA ( n = 30), and established RA, active under DMARD treatment ( n = 31) vs OA. Results: Patients with RA had significantly higher 18 F-FDG uptake in the wall of the carotid arteries (beta 0.27, 95%CI 0.11—0.44, P <0.01) and the aorta (beta 0.47, 95%CI 0.17—0.76, P <0.01) when compared with OA, which persisted after adjustment for traditional CV risk factors. Patients with early RA had the highest 18 F-FDG uptake, followed by patients with established RA and OA respectively. Higher ESR and DAS of 28 joints values were associated with higher 18 F-FDG uptake in all arterial segments. Conclusion: Patients with RA have increased 18 F-FDG uptake in the arterial wall compared with patients with OA, as a possible marker of early atherosclerosis. Furthermore, a higher level of clinical disease activity and circulating inflammatory markers was associated with higher arterial 18 F-FDG uptake, which may support a role of arterial wall inflammation in the pathogenesis of vascular complications in patients with RA.